Successful treatment based on molecular biological assessment of invasive anaplastic lymphoma kinase-positive inflammatory myofibroblastic tumor of the lung - Hironosuke Watanabe; Naoya Yamasaki; Takuro Miyazaki; Keitaro Matsumoto; Tomoshi Tsuchiya; Kuniko Abe; Takeshi Nagayasu (Surgical Case Reports)
Abstract Background Inflammatory myofibroblastic tumor (IMT) of the lung is rare. This disease often shows neoplastic features with anaplastic lymphoma kinase positiveness as well as inflammatory features, such as steroid-responsive immunoglobulin G4 (IgG4)-related sclerosing disease. Since many cases have been reported as advanced, various treatment strategies should be considered based on clinical and biological features of each case. Case presentation We report a 49-year-old male with IMT, which seemed invading the left atrium from preoperative imaging modalities. Serological and pathological examinations from the biopsy specimen revealed high expression of anaplastic lymphoma kinase expression in the tumor. On the other hand, IgG4/IgG ration in the tumor was small, where a therapeutic effect of steroid was not expected, leading to surgical treatment rather than a steroid administration. The tumor was completely resected en bloc with the right lower lobe of the lung and a part of the left atrium. The postoperative course of the patient was uneventful. The patient has remained recurrence free over 5 years from the surgery. Conclusion In this case, preoperative biological assessment prior to the treatment led to a good clinical course. We believe that molecular biological examination is important in the determination of treatment strategy for this rare disease as well as imaging modalities.